Shadow Education in India: Participation and Socioeconomic Determinants. (August 2021) - Kumar, Indal; Chowdhury, Indrani Roy
Although shadow education in India has been in practice for a long time, the scale has grown dramatically in recent years, with the size of the industry ranging between $40 and $70 billion. Drawing from the five rounds of National Sample Survey data sets on education, the study examines the trends and socioeconomic determinants of shadow education participation in India. It also addresses the time burden of shadow education and students' learning outcomes by using the Indian Human Development Survey database. The findings state that households' socioeconomic status, educational level of households' head, urban residence, current schooling levels and type of educational institutions by management are highly significant determinants of participation in shadow education. The analysis further indicates that shadow education is positively associated with learning outcomes at the elementary level and that its contribution is larger in mathematics. However, shadow education costs a couple of hours per day of recreational time of the children (time cost), 40–50% share of household's total educational expenditure, and around 20% share of household's per capita annual consumption expenditure (economic cost).